A comparative study of reduced dose alemtuzumab in matched unrelated donor and related donor reduced intensity transplants. (29th January 2015) - Jardine, Laura; Publicover, Amy; Bigley, Venetia; Hale, Geoff; Pearce, Kim; Dickinson, Anne; Jackson, Graham; Collin, Matthew
Summary In vivo T cell depletion with 100 mg alemtuzumab prevents graft‐versus‐host disease (GVHD) in reduced intensity conditioned transplants but is associated with delayed immune reconstitution, a higher risk of infection and relapse. De‐escalation studies have shown that a reduced dose of 30 mg is as effective as 100 mg in preventing GVHD in matched related donor (MRD) transplants. Dose reduction in matched unrelated donor (MUD) transplants is feasible but the comparative efficacy of alemtuzumab in this setting is not known and opinions vary widely concerning the optimal level of GVHD prophylaxis that should be achieved. Through retrospective analysis we made an objective comparison of MUD transplants receiving an empirically reduced dose of 60 mg, with MRD transplants receiving a 30 mg dose. We observed proportionate levels of alemtuzumab according to dose but an inverse relationship with body surface area particularly in MRD transplants. MUD transplants experienced more acute and chronic GVHD, higher T cell chimerism, more sustained use of ciclosporin and less need for donor lymphocyte infusion than MRD transplants. Thus, doubling the dose of alemtuzumab to 60 mg did not provide equivalent prevention of GVHD after MUD transplant although there was no difference in non‐relapse mortality or survival compared with MRD transplants.